### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

-(x, 0) → x
-(s(x), s(y)) → -(x, y)
*(x, 0) → 0
*(x, s(y)) → +(*(x, y), x)
if(true, x, y) → x
if(false, x, y) → y
odd(0) → false
odd(s(0)) → true
odd(s(s(x))) → odd(x)
half(0) → 0
half(s(0)) → 0
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0))
f(x, 0, z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *(x, z)), f(*(x, x), half(s(y)), z))

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
-(s(x), s(y)) →+ -(x, y)
gives rise to a decreasing loop by considering the right hand sides subterm at position [].
The pumping substitution is [x / s(x), y / s(y)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(x, 0') → 0'
*'(x, s(y)) → +'(*'(x, y), x)
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(x, z)), f(*'(x, x), half(s(y)), z))

S is empty.
Rewrite Strategy: FULL

### (5) SlicingProof (LOWER BOUND(ID) transformation)

Sliced the following arguments:
*'/0
+'/1

### (6) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

S is empty.
Rewrite Strategy: FULL

Infered types.

### (8) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

### (9) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
-, *', odd, half, f

They will be analysed ascendingly in the following order:
*' < f
odd < f
half < f

### (10) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

Generator Equations:
gen_0':s:+':true:false2_0(0) ⇔ 0'
gen_0':s:+':true:false2_0(+(x, 1)) ⇔ s(gen_0':s:+':true:false2_0(x))

The following defined symbols remain to be analysed:
-, *', odd, half, f

They will be analysed ascendingly in the following order:
*' < f
odd < f
half < f

### (11) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)

Induction Base:
-(gen_0':s:+':true:false2_0(0), gen_0':s:+':true:false2_0(0)) →RΩ(1)
gen_0':s:+':true:false2_0(0)

Induction Step:
-(gen_0':s:+':true:false2_0(+(n4_0, 1)), gen_0':s:+':true:false2_0(+(n4_0, 1))) →RΩ(1)
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) →IH
gen_0':s:+':true:false2_0(0)

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (13) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

Lemmas:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)

Generator Equations:
gen_0':s:+':true:false2_0(0) ⇔ 0'
gen_0':s:+':true:false2_0(+(x, 1)) ⇔ s(gen_0':s:+':true:false2_0(x))

The following defined symbols remain to be analysed:
*', odd, half, f

They will be analysed ascendingly in the following order:
*' < f
odd < f
half < f

### (14) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
*'(gen_0':s:+':true:false2_0(+(1, n316_0))) → *3_0, rt ∈ Ω(n3160)

Induction Base:
*'(gen_0':s:+':true:false2_0(+(1, 0)))

Induction Step:
*'(gen_0':s:+':true:false2_0(+(1, +(n316_0, 1)))) →RΩ(1)
+'(*'(gen_0':s:+':true:false2_0(+(1, n316_0)))) →IH
+'(*3_0)

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (16) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

Lemmas:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)
*'(gen_0':s:+':true:false2_0(+(1, n316_0))) → *3_0, rt ∈ Ω(n3160)

Generator Equations:
gen_0':s:+':true:false2_0(0) ⇔ 0'
gen_0':s:+':true:false2_0(+(x, 1)) ⇔ s(gen_0':s:+':true:false2_0(x))

The following defined symbols remain to be analysed:
odd, half, f

They will be analysed ascendingly in the following order:
odd < f
half < f

### (17) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
odd(gen_0':s:+':true:false2_0(*(2, n1173_0))) → false, rt ∈ Ω(1 + n11730)

Induction Base:
odd(gen_0':s:+':true:false2_0(*(2, 0))) →RΩ(1)
false

Induction Step:
odd(gen_0':s:+':true:false2_0(*(2, +(n1173_0, 1)))) →RΩ(1)
odd(gen_0':s:+':true:false2_0(*(2, n1173_0))) →IH
false

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (19) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

Lemmas:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)
*'(gen_0':s:+':true:false2_0(+(1, n316_0))) → *3_0, rt ∈ Ω(n3160)
odd(gen_0':s:+':true:false2_0(*(2, n1173_0))) → false, rt ∈ Ω(1 + n11730)

Generator Equations:
gen_0':s:+':true:false2_0(0) ⇔ 0'
gen_0':s:+':true:false2_0(+(x, 1)) ⇔ s(gen_0':s:+':true:false2_0(x))

The following defined symbols remain to be analysed:
half, f

They will be analysed ascendingly in the following order:
half < f

### (20) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
half(gen_0':s:+':true:false2_0(*(2, n1375_0))) → gen_0':s:+':true:false2_0(n1375_0), rt ∈ Ω(1 + n13750)

Induction Base:
half(gen_0':s:+':true:false2_0(*(2, 0))) →RΩ(1)
0'

Induction Step:
half(gen_0':s:+':true:false2_0(*(2, +(n1375_0, 1)))) →RΩ(1)
s(half(gen_0':s:+':true:false2_0(*(2, n1375_0)))) →IH
s(gen_0':s:+':true:false2_0(c1376_0))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (22) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

Lemmas:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)
*'(gen_0':s:+':true:false2_0(+(1, n316_0))) → *3_0, rt ∈ Ω(n3160)
odd(gen_0':s:+':true:false2_0(*(2, n1173_0))) → false, rt ∈ Ω(1 + n11730)
half(gen_0':s:+':true:false2_0(*(2, n1375_0))) → gen_0':s:+':true:false2_0(n1375_0), rt ∈ Ω(1 + n13750)

Generator Equations:
gen_0':s:+':true:false2_0(0) ⇔ 0'
gen_0':s:+':true:false2_0(+(x, 1)) ⇔ s(gen_0':s:+':true:false2_0(x))

The following defined symbols remain to be analysed:
f

### (23) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol f.

### (24) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

Lemmas:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)
*'(gen_0':s:+':true:false2_0(+(1, n316_0))) → *3_0, rt ∈ Ω(n3160)
odd(gen_0':s:+':true:false2_0(*(2, n1173_0))) → false, rt ∈ Ω(1 + n11730)
half(gen_0':s:+':true:false2_0(*(2, n1375_0))) → gen_0':s:+':true:false2_0(n1375_0), rt ∈ Ω(1 + n13750)

Generator Equations:
gen_0':s:+':true:false2_0(0) ⇔ 0'
gen_0':s:+':true:false2_0(+(x, 1)) ⇔ s(gen_0':s:+':true:false2_0(x))

No more defined symbols left to analyse.

### (25) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)

### (27) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

Lemmas:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)
*'(gen_0':s:+':true:false2_0(+(1, n316_0))) → *3_0, rt ∈ Ω(n3160)
odd(gen_0':s:+':true:false2_0(*(2, n1173_0))) → false, rt ∈ Ω(1 + n11730)
half(gen_0':s:+':true:false2_0(*(2, n1375_0))) → gen_0':s:+':true:false2_0(n1375_0), rt ∈ Ω(1 + n13750)

Generator Equations:
gen_0':s:+':true:false2_0(0) ⇔ 0'
gen_0':s:+':true:false2_0(+(x, 1)) ⇔ s(gen_0':s:+':true:false2_0(x))

No more defined symbols left to analyse.

### (28) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)

### (30) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

Lemmas:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)
*'(gen_0':s:+':true:false2_0(+(1, n316_0))) → *3_0, rt ∈ Ω(n3160)
odd(gen_0':s:+':true:false2_0(*(2, n1173_0))) → false, rt ∈ Ω(1 + n11730)

Generator Equations:
gen_0':s:+':true:false2_0(0) ⇔ 0'
gen_0':s:+':true:false2_0(+(x, 1)) ⇔ s(gen_0':s:+':true:false2_0(x))

No more defined symbols left to analyse.

### (31) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)

### (33) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

Lemmas:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)
*'(gen_0':s:+':true:false2_0(+(1, n316_0))) → *3_0, rt ∈ Ω(n3160)

Generator Equations:
gen_0':s:+':true:false2_0(0) ⇔ 0'
gen_0':s:+':true:false2_0(+(x, 1)) ⇔ s(gen_0':s:+':true:false2_0(x))

No more defined symbols left to analyse.

### (34) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)

### (36) Obligation:

TRS:
Rules:
-(x, 0') → x
-(s(x), s(y)) → -(x, y)
*'(0') → 0'
*'(s(y)) → +'(*'(y))
if(true, x, y) → x
if(false, x, y) → y
odd(0') → false
odd(s(0')) → true
odd(s(s(x))) → odd(x)
half(0') → 0'
half(s(0')) → 0'
half(s(s(x))) → s(half(x))
if(true, x, y) → true
if(false, x, y) → false
pow(x, y) → f(x, y, s(0'))
f(x, 0', z) → z
f(x, s(y), z) → if(odd(s(y)), f(x, y, *'(z)), f(*'(x), half(s(y)), z))

Types:
- :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
0' :: 0':s:+':true:false
s :: 0':s:+':true:false → 0':s:+':true:false
*' :: 0':s:+':true:false → 0':s:+':true:false
+' :: 0':s:+':true:false → 0':s:+':true:false
if :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
true :: 0':s:+':true:false
false :: 0':s:+':true:false
odd :: 0':s:+':true:false → 0':s:+':true:false
half :: 0':s:+':true:false → 0':s:+':true:false
pow :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
f :: 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false → 0':s:+':true:false
hole_0':s:+':true:false1_0 :: 0':s:+':true:false
gen_0':s:+':true:false2_0 :: Nat → 0':s:+':true:false

Lemmas:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)

Generator Equations:
gen_0':s:+':true:false2_0(0) ⇔ 0'
gen_0':s:+':true:false2_0(+(x, 1)) ⇔ s(gen_0':s:+':true:false2_0(x))

No more defined symbols left to analyse.

### (37) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
-(gen_0':s:+':true:false2_0(n4_0), gen_0':s:+':true:false2_0(n4_0)) → gen_0':s:+':true:false2_0(0), rt ∈ Ω(1 + n40)